Production of H2-rich syngas from excavated landfill waste through steam co-gasification with biochar. (15th September 2020) - Zaini, Ilman Nuran; Gomez-Rueda, Yamid; García López, Cristina; Ratnasari, Devy Kartika; Helsen, Lieve; Pretz, Thomas; Jönsson, Pär Göran; Yang, Weihong
Abstract: Gasification of excavated landfill waste is one of the promising options to improve the added-value chain during remediation of problematic old landfill sites. Steam gasification is considered as a favorable route to convert landfill waste into H2 -rich syngas. Co-gasification of such a poor quality landfill waste with biochar or biomass would be beneficial to enhance the H2 concentration in the syngas, as well as to improve the gasification performance. In this work, steam co-gasification of landfill waste with biochar or biomass was carried out in a lab-scale reactor. The effect of the fuel blending ratio was investigated by varying the auxiliary fuel content in the range of 15–35 wt%. Moreover, co-gasification tests were carried out at temperatures between 800 and 1000 °C. The results indicate that adding either biomass or biochar enhances the H2 yield, where the latter accounts for the syngas with the highest H2 concentration. At 800 °C, the addition of 35 wt% biochar can enhance the H2 concentration from 38 to 54 vol%, and lowering the tar yield from 0.050 to 0.014 g/g-fuel-daf. No apparent synergetic effect was observed in the case of biomass co-gasification, which might cause by the high Si content of landfill waste. In contrast, the H2 production increases non-linearly with the biochar share in the fuel, which indicates that a significant synergetic effect occurs during co-gasification due to the reforming of tar over biochar. Increasing the temperature of biochar co-gasification from 800 to 1000 °C elevates the H2 concentration, but decreases the H2 /CO ratio and increases the tar yield. Furthermore, the addition of biochar also enhances the gasification efficiency, as indicated by increased values of the energy yield ratio. Highlights: Steam co-gasification of landfill waste with biochar or biomass was carried out. No clear synergetic effect was observed in the case of biomass co-gasification. The addition of biochar promotes synergetic effects on the H2 yield production. Addition of biochar produces higher H2 yield than that of biomass.